2009
DOI: 10.1038/sc.2009.161
|View full text |Cite
|
Sign up to set email alerts
|

Psychological intervention during spinal rehabilitation: a preliminary study

Abstract: Study design: A repeated measures, non-randomised controlled trial. Objective: To examine the effectiveness of individualised cognitive behaviour therapy (CBT) on the psychological adjustment of patients undergoing rehabilitation for newly acquired spinal cord injury. Setting: South Australian Spinal Cord Injury Service, Hampstead Rehabilitation Centre, South Australia, Australia. Methods: Eleven participants received individual CBT as part of their spinal rehabilitation. Selfreported levels of depression, anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 17 publications
1
51
0
Order By: Relevance
“…Duchnick et al (2009) reported a sample size estimate of 0.80 with an alpha error protection rate of 0.05, while Dorstyn et al (2010) reported their study to be underpowered. Sample sizes of all the studies reported herein ranged from 18 to 296, with an average sample size of 76.1.…”
Section: Study Size and Qualitymentioning
confidence: 92%
See 1 more Smart Citation
“…Duchnick et al (2009) reported a sample size estimate of 0.80 with an alpha error protection rate of 0.05, while Dorstyn et al (2010) reported their study to be underpowered. Sample sizes of all the studies reported herein ranged from 18 to 296, with an average sample size of 76.1.…”
Section: Study Size and Qualitymentioning
confidence: 92%
“…Dorstyn et al (2010) reported providing amitriptyline to five participants in the treatment group for distress, and five participants in the control group for neuropathic pain. Participants in both the control and treatment groups of the Kahan et al (2006) and Kemp et al (2004) studies were prescribed antidepressants on an individual basis, with paroxetine and sertraline most commonly prescribed.…”
Section: Combined Pharmacological Treatmentmentioning
confidence: 98%
“…96 On the positive side, all studies showed a significant decrease of depressive symptoms during the intervention, although this effect was not always maintained at follow-up. 93 In one study, 94 subgroup analyses showed that for people with baseline levels of depression in the clinical range, the CBT group improved more than the control group, suggesting that CBT might be more effective in people with more severe mental health disorders. Only one study examined possible mechanisms of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…52 We found six psychological intervention studies primarily aimed at improving mental health of people with SCI (Table 5). 54,[93][94][95][96][97] The study design of most studies was weak; only one was a randomized controlled trial. 97 Other studies used people as controls who were treated in earlier years or elsewhere, 94-96 who were not eligible for the intervention 93 or who declined the intervention.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation